Application of lean healthcare in hospital services: a review of the literature (2007 to 2017) - José Daniel Rodrigues Terra; Fernando Tobal Berssaneti (Production)
Abstract Paper aims The demand for quality health services is increasing and the efficiency in hospitals is related to the continued improvement in their processes and services. Faced with this problem, this study aimed to perform a literature review of the application of lean health care to hospital services. Originality Link between theory and practice, helping health professionals in their routine. Research method The concepts of bibliometrics were used. The databases that make up the sample are ISI Web of Science, Scopus, Lilacs, PubMed, and Cinahl; all the articles were in the ISI Web of Science database. Main findings The analyses suggest that the continuous improvement in processes and in the quality of the services offered are factors that influence the development of teams concerned with patient safety. Implications for theory and practice Shows the results and difficulties encountered by hospitals with the implementation of lean methodologies.